Universal Strategy for Improving the Sensitivity of Detecting Volatile Organic Compounds by Patterned Arrays. (15th July 2020) - Liu, Lu; Xiong, Wei; Cui, Linfeng; Xue, Zhenjie; Huang, Chuanhui; Song, Qian; Bai, Wanqiao; Peng, Yage; Chen, Xiangyu; Liu, Keyan; Zhang, Shuwei; Wen, Lei; et al.
Abstract: The diffusion of target analytes is a determining factor for the sensitivity of a given gas sensor. Surface adsorption results in a low‐concentration region near the sensor surface, producing a concentration gradient perpendicular to the surface, and drives a net flux of molecules toward solid reactive reagents on the sensor surface, that is, vertical diffusion. Here, organic semiconductor supramolecules were patterned into micromeshed arrays to integrate vertical and horizontal diffusion pathways. When used as a gas sensor, these arrays have an order of magnitude higher sensitivity than traditional film‐based sensors. The sensor sensitivity ramp down with the increase in coverage density of reactive reagents, yielding two linear regions demarcated by 0.3 coverage, which are identified by the experimental results and simulations. The universal nature of template‐assisted patterning allows adjustments in the composition, size, and shape of the constituent material, including nanofibers, nanoparticles, and molecules, and thus serves to improve the sensitivity of gas sensors for detecting various volatile organic compounds. Abstract : Molecular diffusion ultimately determines the sensitivity of gas sensors, whose driving force is directly proportional to the analyte concentration gradient. When the vertical diffusion was switched to the integration of vertical and horizontal diffusion, the gas sensors fabricated on patterned arrays displayed an order of magnitude higher sensitivity than their counterpart film‐based sensors.